Clinical Prediction of Inadequate Vault in Eyes With Thick Lens After Implantable Collamer Lens Implantation Using Iris Morphology - Yang, Zhikun; Meng, Lihui; Zhao, Xinyu; Chen, Youxin; Luo, Yan (Frontiers in Medicine, 2022)
Background Obtaining an ideal vault is crucial in the implantable collamer lens (ICL) surgery. Prediction of the vault value is difficult since it requires the integration of multiple factors. The purpose of this study was to investigate the association between the iris shape and vault value in eyes with thick lens. Methods The study was conducted in Peking Union Medical College Hospital. Patients who received ICL V4c between 2017 and 2021 were screened. Eyes with thick lens (> 4.0mm) and abnormal iris shape (concave or convex) were included. The preoperative biometric parameters and postoperative vault value were compared between eyes with concave shape group and convex shape group. The relationship between various factors and vault was assessed by spearman rank analysis and multiple linear regression analysis. Representative cases our strategies to deal with the abnormal vault were demonstrated. Results 28 eyes of 14 patients with thick lens and concave or convex shape iris were eventually included, with 14 eyes of 7 patients in group 1 (concave shape iris) and the other 14 eyes of 7 patients in group 2 (convex shape iris). The mean vault of group 1 was (0.16±0.07) mm, which was significantly lower than (0.88±0.13) mm in group 2. Multiple linear regression analysis showed iris shape (P<0.001) was only the explanatory variables associated with the postoperative vault. In group1, 4 eyes showed extremely large ACA, requiring a secondary surgical intervention. So all of them underwent ICL exchange for a larger ICL. In group2, the ICL was implanted in a vertical or oblique position to avoid or rescue an extremely large vault. Conclusion Concave shape iris had a higher risk of low vault and convex shape iris were more likely to demonstrate high vault in eyes with thick lens. Exchanging ICL for the larger size and adjusting ICL to the vertical or oblique orientation are good option to rescue the low or high vault respectively.